The Rise and Decline of American Religious Freedom - Steven D. Smith (Harvard University Press, 2014)
In good conscience I can concede, cheerfully, this much: the oft- told, much beloved story of religious freedom in America is not wholly false. In fact, the story contains a number of partial truths. And yet a collection of partial truths can combine, as we know, to make up a tale that is, in the aggregate, profoundly misleading. As in this instance.The story of American religious freedom has been told in many places and many ways. But most of the venerable tellings include several or all of the following themes: 1. Americans as Enlightened innovators. When Americans committed themselves in their new Constitution to church- state separation and the free exercise of religion, they were initiating a novel and even radical â€œlively experiment.â€ Or so it is typically supposed. For centuries, under the pattern and practices of what we sometimes describe as â€œChristendom,â€ po liti cal and religious authorities had imposed religious orthodoxies on their subjects and had repressed dissent through laws punishing heresy, blasphemy, and apostasy. This orientation was on macabre display in the Inquisition and in the execution of presumed heretics, such as the defi ant En glish Protestants burned at the stake under Bloody Mary and celebrated in John Foxeâ€™s legendary Book of Martyrs. The American found ers, freed up by the Enlightenment, boldly broke from this centuries- old pattern. They thereby achieved what the eminent historian of religion Sidney Mead described as â€œone of the two most profound revolutions that had occurred in the history of the church.â€1 (The fi rst revolution, Mead thought, was the Constantinian revolution that had initiated Christendom fourteen centuries earlier. So the second revolutionâ€” the American oneâ€” in eff ect overthrew the fi rst, Christian revolution.)